Social Anxiety Modulates Risk Sensitivity through Activity in the Anterior Insula - Tang, Grace S.; van den Bos, Wouter; Andrade, Eduardo; McClure, Samuel (Frontiers in Neuroscience, 2012)
Decision neuroscience offers the potential for decomposing differences in behavior across individuals into components of valuation intimately tied to brain function. One application of this approach lies in novel conceptualizations of behavioral attributes that are aberrant in psychiatric disorders. We investigated the relationship between social anxiety and behavior in a novel socially determined risk task. Behaviorally, higher scores on a social phobia inventory (SPIN) among healthy participants were associated with an increase in risky responses. Furthermore, activity in a region of the dorsal anterior insula (dAI) scaled in proportion to SPIN score in risky versus non-risky choices. This region of the insula was functionally connected to areas in the intraparietal sulcus and anterior cingulate cortex that were related to decision-making across all participants. Overall, social anxiety was associated with decreased risk aversion in our task, consistent with previous results investigating risk taking in many everyday behaviors. Moreover, this difference was linked to the anterior insula, a region commonly implicated in risk attitudes and socio-emotional processes.